2010
DOI: 10.1590/s0102-86502010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic programming of lipid profile and reproductive organs weight by leptin treatment on early life

Abstract: PURPOSE: To evaluate whether the neonatal leptin treatment during the first days of life can program the male reproductive organs weight and the lipid profile. METHODS: At birth 6 dams were divided into 2 groups: Leptin - each pup was injected with 50μL of recombinant rat leptin (80ng/g BW, sc), for the first 10 d of lactation; Control - each pup received the same volume of saline. After weaning, all pups received unlimited access to food until 190 days of age when they were killed. Values are given as mean ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Investigators using neonatal leptin treatment given to offspring of normally fed dams have shown increased adiposity and leptin and insulin resistance in offspring in later life [3335]. The present result shows that the reverse can hold true.…”
Section: Discussionsupporting
confidence: 51%
“…Investigators using neonatal leptin treatment given to offspring of normally fed dams have shown increased adiposity and leptin and insulin resistance in offspring in later life [3335]. The present result shows that the reverse can hold true.…”
Section: Discussionsupporting
confidence: 51%
“…In fact, in certain rodent and human gliomas, the phosphoinositide-3-kinase (PI3K-Akt) pathway seems to activate ABCG2 transporters, whereas the loss of another signaling molecule phosphatase and tensin homologue deleted on chromosome 10 (PTEN) enhances ABCG2 expression [228,246]. In addition, specific pluripotent CSCs regulatory molecules, such as Thy-1, c-kit, Oct-4, and others maintains renewal and totipotency and are suspected to "cross-talk" with the transcriptional regulation of some MDR-ABC transporters such as ABCB1, ABCG2 and ABCC1 [246,247]. Further characterization of ABC transporters will clarify their role in the modulation of key regulatory pathways involved in stem cell biology.…”
Section: Abc Transporters In Cancer Stem Cellsmentioning
confidence: 99%
“…However, leptin concentrations in the milk progressively increased during lactation, suggesting that this change is related to differences in leptin production by epithelial cells in the mammary gland (50). In rats, the pup's immature stomach can absorb orally provided leptin (50), and early exposure to high leptin levels increases adult body weight (51). Leptin also seems to influence neuronal growth in the hypothalamus (52).…”
Section: Breast Milkmentioning
confidence: 99%